Cyber security fun race / Mazlyda Abd Rahman ... [et al.] - Abd Rahman, Mazlyda; Zamani, Nur Diana; Jaafar, Nur Huda; Mokhtar, Rashidah; Ismail, Zuriati (Faculty of Computer and Mathematical Sciences, 2023)
The Explore race has always been a popular outdoor activity among people of all ages. It serves as a form of escape from our everyday routines. It is also time for us to get acquainted with other community members. An online exploration race concept has been introduced in this project due to weather, physical ability, safety, and logistics restrictions. The concept is based on the traditional explore race, which calls for both knowledge and physical prowess to travel about and perform the tasks that are presented at each checkpoint. The primary and secondary school students are intended users of this online explore race. Five (5) checkpoints have been established with tasks relating to the theme of cyber security awareness during this online exploration race called the "Cyber Security Fun Race". We use gamification aspects to raise cyber security awareness among participants and improve user experience. Media such as video and infographics are included where possible to increase participant knowledge while playing the game. In order to receive the highest possible score and win the race, participants must finish all the tasks. This online competitive race offers a variety of advantages. As long as there is a strong internet connection, it can be accessed at any time and from any location. Additionally, since it does not take physical stamina to walk around, those who lack it do not lose out. This entertaining race is not only appropriate for group involvement, but it is also enjoyable for lone players. The content can be continually updated at very little cost since it is online. Our goal is to impart knowledge in a fun way.